Exploring the perspectives of health professionals in a rural district hospital in Achham, Nepal on the role of daily continuing medical education (CME) - Gauchan, Bikash; Upreti, Apil; Upreti, Amit; Serchan, Rekha; Schwarz, Dan (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: A rural district hospital in Achham district of Nepal has daily continuing medical education (CME) sessions. These sessions are attended by health professionals from different departments providing healthcare services. This study aims to explore the perspectives of health professionals in a rural district hospital in Achham of Nepal on the role of daily CME on the quality of clinical care and on their professional development in order to find the impact of daily CME. Method: A qualitative study was conducted in a rural district hospital in Achham, Nepal. Semi-structured interviews were conducted with 10 participants who were health professionals, aged 20-60 years old and recruited through a convenience sampling method in 2020. The data were analyzed using thematic content analysis (TCA). Result: All the participants shared the importance, strengths, and challenges of daily CME sessions and recommended to improve the CME sessions. All the participants had clear perceptions of positive impact of daily CME to refresh their knowledge, create a learning environment, improve presentation and speaking skills, learn clinical protocols, improve their professional development, share ideas to improve patient care and create a platform to share quality improvement steps. The diverse educational background of health professionals, CME curriculum, and time allocation of physicians for CME sessions remain challenges of daily CME. The participants recommended adding more topics in the CME curriculum and revise CME facilitation methods. Conclusion: District hospitals in rural Nepal can conduct daily CME sessions to upgrade the clinical knowledge and skills of health professionals and improve clinical services. Further studies are required to establish robust evidence about the impact of daily CME sessions.